Pengaruh Kualitas Jaringan terhadap Kepuasan Pelanggan dengan Kepercayaan sebagai Variabel Intervening pada Pengguna Jaringan Indihome PT Telkom Kecamatan Pancung Soal - Anzari, Aulia Rahman; Veri, Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study investigates the effect of network quality on IndiHome customer satisfaction in Pancung Soal District with trust as an intervening variable. This quantitative study used a purposive sampling technique to select 50 respondents with specific criteria, namely a minimum membership period of 6 months, to ensure that the selected sample had sufficient experience in using the service. Data collected through a Likert scale questionnaire were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results of the study indicate that: (1) Network quality has a direct positive and significant effect on customer satisfaction; (2) Network quality also has a positive and significant effect on trust; however (3) Trust does not have a significant effect on customer satisfaction and (4) Trust does not act as an intervening variable that mediates the relationship between network quality and satisfaction. These findings indicate that customer satisfaction is more directly determined by the technical performance of the network than by the trust factor. The practical implications of this study suggest that PT Telkom should prioritize improving network quality directly to increase customer satisfaction.